Experimental Investigation Of Pedestrian Flow Through A Corridor With Corner - Adenan, SSaidatul Husna Mohamed (Universiti Sains Malaysia, 2017)
Walking speed of pedestrians is governed by many influencing factors such as density of pedestrian, corridor facilities and so on. Since pedestrian have wide range of needs and abilities, several approaches for determining pedestrian dynamics have been done. Federal Highway Administration (FHWA) Manual on Uniform Traffic Control Devices for Streets and Highways and Highway Capacity Manual 2000 includes a walking speed of 1.2 m/s with zero elderly pedestrian involved. Many research studies have been done in investigating the pedestrian dynamics which includes modelling and simulating. However, so far not much attention has been paid to their qualitative measurements. Besides, the study of pedestrian walking speed on corridor with corner is relatively rare. Therefore, this study is carried out under two main objectives which are to determine empirically walking speed of pedestrian for unidirectional free flows at corridor with corner and also to quantify the walking speed of pedestrian by gender. In this paper, we review the recent developments in pedestrian dynamics, by the implementation of experiments under laboratory conditions with up to 60 pedestrians and extraction of trajectories by video analysis in complex facilities of corridor with corner, e.g. 60° corner, 90° corner and 135° corner. A straight corridor with 180° is used as a baseline in this experiment. The data is analysed for each task given in which different number of pedestrians and width of corridor are used for each corner. Surprisingly, the result shows that average walking speed of male is lower than average walking speed of female and applied at almost all tasks. Within three different corners, 135° corner facility shows a constant average walking speed of pedestrian even though the numbers of pedestrians are increased. To quantify the second objective in this study, the cumulative frequency graph of corridor walkway was plotted to determine 15th percentile and 50th percentile of walking speed both for female and male pedestrians relative to parameters involved. The results are of particular importance for designing the structure especially at walking corridor and also beneficial for the design of an emergency response plan.